Bleeding Time and Surgical Blood Losses in Nonhemorrhagic People - Roskam, J (Thrombosis and Haemostasis, 1969)
1. Discussion of various clinical trials upon the hemostatic properties of adrenochrome derivatives suggest a possible correlation between bleeding time and hemostatic plug resistance.2. It is hoped that this hypothesis will result in new experiments in man and in laboratory animal which might improve general non-specific hemostatic therapy, more especially in order to lessen preventively surgical blood losses.